ATIM-38. GLITIPNI: A PHASE 1B CLINICAL TRIAL COMBINING SURGICAL RESECTION WITH DIRECT INTRACEREBRAL INJECTION OF IMMUNE CHECKPOINT INHIBITORS IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (11th November 2019) - Duerinck, Johnny; Awada, Gil; Katharina Schwarze, Julia; Dufait, Ines; Peeters, Stephanie; Seynave, Laura; Van Binst, Anne-marie; Everaert, Hendrik; Michotte, Alex; Rogiers, Anne; Van Velthoven, Vera; Neyns, Bart
Abstract: INTRODUCTION: Intravenous (iv) administration of PD-1 blocking mAb is largely ineffective for the treatment of recurrent glioblastoma (rGB). Combination of iv-ipilimumab (IPI) plus nivolumab (NIVO) is associated with a high incidence of irAE. Intracerebral (ic) administration of immune-checkpoint inhibiting mAb following the resection of rGB could be a more effective and safer alternative to iv-dosing. METHODS: Patients underwent maximal safe resection of their rGB followed by ic-injection of 10mg IPI (cohort-1) or 5mg IPI plus 10mg NIVO (cohort-2) in the wall of the resection cavity. In both cohorts 10mg nivolumab was administered iv for a max of 6 doses, starting 1 day pre-operatively. RESULTS: 21 pts were included (3 in C-1, 18 in C-2; 8F/13M; median age 56y [range 38–72]; 17 de novo GB, 4 secGB). All patients underwent maximal safe surgical resection followed by ic-injection of IPI and NIVO as planned. Median number of iv-administrations of NIVO was 5 (range 1–8). Treatment was generally well tolerated. Postoperatively, 2 patients experienced a G3 symptomatic increase in perilesional cerebral edema with neurological deterioration, reversible upon steroid treatment. One patient had worsening neurological symptoms related to an inflammatory intracerebral cyst at the resection site, requiring surgical decompression 4 months post-study treatment. Most frequent AEs were fatigue (2pts G3, 8pts G2), postoperative fever (11pts G1) and headache (3pts G2); 1pt developed G3 pneumonitis. No other immune-related AEs or treatment-related deaths occurred. After median follow-up of 60 weeks, median PFS is 14.4 weeks (95% CI 11.2–17.6); 11/21 patients are alive, and 1- and 2y-OS% are respectively 46% (95% CI 19- 73%), and15% (95% CI 0–42%). CONCLUSION: This is the first study demonstrating the safety and activity of combined surgical resection of rGB with local intracerebral administration of immune checkpoint-inhibiting mAb. Survival compares favorably to historical controls justifying further investigation of this experimental therapy.